2013
DOI: 10.1021/cs400032e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Cu Nanoparticles in SBA-15 Functionalized with Carboxylic Acid Groups and Their Application in the Water–Gas Shift Reaction

Abstract: SBA-15 functionalized with carboxylic acid groups has been used to synthesize Cu nanoparticles 2–6 nm in average size with 7.6–25.2 wt % Cu. In this study, the formation mechanism and characterization of Cu nanoparticles at various Cu concentrations are described. For samples with 7.6 and 11.9 wt % Cu, linear [Cuδ+···Oδ−···Cuδ+] n chains generated through calcination are possibly located inside the SBA-15 channels. When the concentration of Cu is increased to 18.3 wt %, the Cu2(OH)3NO3 species becomes the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…This result indicated that the copper in the structure of DCS Ns was not in the form of Cu 2 O or CuO. 32 In the second shells, besides the Cu-Cu shell with a bond distance of 2.88 and a coordination number of 0.6, the Cu-Si shell with a bond distance of 3.17 and a coordination number of 1.5 was also observed, conrming that Cu was incorporated into the silica framework, 3 forming Si-O-Cu bonds. As for DCAS Ns, the Cu-Al shell with a bond distance of 3.15Å emerged with the introduction of Al and the bond distance and coordination number of the Cu-Si shell changed to 3.20 and 0.4, respectively.…”
Section: Catalyst Characterizationmentioning
confidence: 91%
“…This result indicated that the copper in the structure of DCS Ns was not in the form of Cu 2 O or CuO. 32 In the second shells, besides the Cu-Cu shell with a bond distance of 2.88 and a coordination number of 0.6, the Cu-Si shell with a bond distance of 3.17 and a coordination number of 1.5 was also observed, conrming that Cu was incorporated into the silica framework, 3 forming Si-O-Cu bonds. As for DCAS Ns, the Cu-Al shell with a bond distance of 3.15Å emerged with the introduction of Al and the bond distance and coordination number of the Cu-Si shell changed to 3.20 and 0.4, respectively.…”
Section: Catalyst Characterizationmentioning
confidence: 91%
“…To strike ab alance between the kinetics and thermodynamics, this reaction is industrially operated in two stages:o ne at lower temperatures ( % 200-250 8C) catalyzed by Cu-Zn catalysts;t he other at higher temperatures ( % 350-450 8C) catalyzed by Fe-Cr catalysts. [1][2][3][4] In the high-temperature WGS reaction, Ni is widely studied as ac andidate to replaceF e-Cr catalysts, whicha re known to be toxic owing to theC rc ontent. [5] Despite the high catalytic activity of Ni at high temperatures, it catalyzes the undesirable methanation side reaction, which decreasest he H 2 selectivity and hinders the commercialization of Ni-basedc atalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the high cost and limited availability of precious metals, research into formulating less‐expensive WGS catalysts by employing non‐noble metals and their oxides is thriving. Copper‐based materials have been studied as catalysts for the WGS reaction, either in the form of spinel mixed oxides or supported on a variety of oxides . Indeed, copper‐based catalysts, usually in combination with ZnO and alumina, have been used commercially for low‐temperature WGS .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, copper‐based catalysts, usually in combination with ZnO and alumina, have been used commercially for low‐temperature WGS . The activity of silica‐supported copper catalysts for the WGS reaction has also been studied, showing that a high dispersion of the copper phase is highly advantageous. Because copper is known to sinter rapidly, the preparation method and interaction between the silica support and copper phase play key roles in the development of a highly dispersed active phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation